Radionuclide contamination and nutritional evaluation of the wheat mostly used in the Republic of North Macedonia - Aleksandra Angeleska; Radmila Crceva-Nikolovska; Elizabeta Dimitrieska-Stojkovikj; Zehra Hajrulai-Musliu; Biljana Stojanovska-Dimzoska; Ana Angelovska (University of Banjaluka, Faculty of agriculture, 2022)
Wheat is one of the world's most commonly consumed cereal grains. It originates from a type of grass (Triticum) that is grown in countless varieties worldwide. Bread wheat or common wheat is a primary species. Several other closely related species include durum, spelt, emmer, einkorn, and Khorasan wheat. In addition to being a major source of starch and energy, wheat also provides substantial amounts of a number of components which are essential or beneficial for health, notably proteins, vitamins (notably B vitamins), dietary fibres, and phytochemicals. Wheat is a basic food product of Macedonian population. This study is mainly focused on measuring the concentration of radioactivity due to natural radioactive nuclides (226 Ra, 232 Th, 40 K) in wheat grain samples, as well as on determining the quality of wheat used in daily diet. In addition, in this study we calculated radiation hazard indices (radium equivalent activity and internal hazard index) in the wheat sample. Average activity concentrations of 226 Ra, 232 Th, and 40 K in the wheat samples were 0.57±0.14; 0.39±0.11; 96.55±0.86 (Bq·kg-1), respectively. The radiation hazard indices were calculated for all samples in this study where mean values did not exceed safety limits, pointing out to negligible radiation hazard arising from terrestrial radionuclides that are naturally present in wheat. In terms of quality, we confirmed that all tested samples meet the requirements regarding quality in accordance with the laws in our country.
Keywords: radioactivity in wheat, radionuclides, gamma spectrometer, quality control